Impact of Civic Education on Community-Led Crime Control Model in FCT-Abuja, Nigeria - Sule Omeiza Adebayo; Blessing Ikechi Onyedum; Chukwuma Victoria Azuka; Emmanuel Lucas Nwachukwu (Darul Yasin Al Sys, 2026)
Crime and insecurity remain critical challenges in Nigeria’s Federal Capital Territory, Abuja, requiring innovative community-based approaches to complement conventional policing strategies. This study examined the influence of civic education on community-led crime control participation in FCT-Abuja. A quantitative survey design was employed, involving 400 adult residents selected through stratified random sampling across the six Area Councils. Data were collected using a structured questionnaire with dichotomous response items measuring exposure to civic education and participation in community crime control activities. The data were analysed using the chi-square test of independence at the 0.05 significance level. The findings revealed that 69.6% of respondents had been exposed to civic education programmes, while 65.2% participated in community crime control activities. The chi-square analysis showed a statistically significant relationship between civic education exposure and crime control participation, χ² = 56.842, p < .001. Residents exposed to civic education were more likely to participate in crime control activities (76.5%) than unexposed residents (39.3%), representing a 37.2 percentage-point difference. These findings indicate that civic education significantly strengthens community-led participation in crime control in FCT-Abuja. The study contributes to security and civic education literature by demonstrating the relevance of civic awareness in promoting community security engagement. It recommends that policymakers expand civic education coverage, diversify delivery platforms, and sustain civic education programming to strengthen community security capacity across all Area Councils.